LEXICAL-SEMANTIC AND STYLISTIC FEATURES OF THE COVERAGE OF SINO-TAIWAN RELATIONS IN AMERICAN PUBLICISTICS (FROM 2021 TO 2023) - ВЕРЕМЧУК, Ельдар; ТКАЧУК, Тарас (Київський національний університет імені Тараса Шевченка, 2023)
The scientific work aims to characterise the lexical-semantic and stylistic features of coverage of the current state of Sino-Taiwanese relations in the American press. The research material consists of articles taken from such newspapers as The New York Times, The Washington Post, USA Today, Newsweek magazine and publications of the CNN news agency. Methods of the research: contextual analysis (for the most objective characterization of linguistic features of publicistics in the United States); lexical-semantic analysis (an overview of the general position of the authors of newspaper articles regarding the “Taiwanese problem”, to identify and analyze comparisons and antitheses as common stylistic devices in the press); interpretive method (to form the authors’ assessment of the factors that determined the use of certain lexical constructions according to certain aspects of recent Sino-Taiwanese relations). Scientific novelty: for the first time, the authors have carried out a lexico-semantic analysis of Sino-Taiwanese relations based on English-language British and American publicistics regarding the current geopolitical challenges. Conclusions. Idioms in coverage of the “Taiwanese problem” are primarily used to indicate the role of the USA and China in East Asia, as well as to compare the situation around Taiwan with Russia’s attack on Ukraine. The basic idea is Washington’s consideration of the “Taiwanese problem” as a potential bridgehead for a possible confrontation between the two “superpowers”. As for stylistic features, the analysis enabled the researchers to separate numerous epithets, comparisons, antitheses, metaphors and establish their prevalence in the coverage of Sino-Taiwanese relations, as well as personifications, tautologies, and irony, used by the authors of publications less often.

Метою наукової роботи є характеристика лексико-семантичних і стилістичних особливостей висвітлення сучасного стану китайсько-тайванських відносин в американській пресі. Матеріалом дослідження є статті з газет The New York Times, The Washington Post, USA Today, журналу Newsweek, а також публікації агентства новин CNN за період 2021–2023 рр. Методи дослідження: контекстуальний аналіз (для максимально об’єктивної характеристики мовних особливостей публіцистики Сполучених Штатів); лексико-семантичний аналіз (у контексті огляду загальної позиції авторів газетних статей щодо «тайванської проблеми», виявлення й аналізу порівнянь та антитез як поширених у пресі стилістичних засобів); метод інтерпретації (для формування власної оцінки факторів, що зумовлюють вживання певних лексичних конструкцій відповідно до окремих аспектів сучасних китайсько-тайванських відносин). Наукова новизна: уперше здійснено лексико-семантичний аналіз китайсько-тайванських відносин на базі англомовної британської та американської публіцистики з огляду на геополітичні виклики сучасності. Висновки. Ідіоми у висвітленні «тайванської проблеми» передусім застосовуються для позначення ролі США і Китаю у Східній Азії, а також для порівняння ситуації навколо Тайваню з нападом Росії на Україну. Основоположною ідеєю виступає розгляд Вашингтоном «тайванської проблеми» як потенційного плацдарму для можливого протистояння двох «наддержав». Щодо стилістичних особливостей, то проведений аналіз дав змогу відокремити численні епітети, порівняння, антитези, метафори та встановити їх превалювання у висвітленні китайсько-тайванських відносин, а також персоніфікації, тавтології та прийоми іронії, які використовуються авторами публікацій дещо рідше.
ЛЕКСИКО-СЕМАНТИЧНІ ТА СТИЛІСТИЧНІ ОСОБЛИВОСТІ ВИСВІТЛЕННЯ КИТАЙСЬКО-ТАЙВАНСЬКИХ ВІДНОСИН В АМЕРИКАНСЬКІЙ ПУБЛІЦИСТИЦІ (З 2021 ПО 2023 Р.)
Keywords: англійська мова; преса; лексика; стилістичні засоби; міжнародні відносини; Китай; Тайвань; English; press; vocabulary; stylistic means; international relations; China; Taiwan